Occupational Health Hazards of Women Tailors in Valliyur Block, Tirunelveli District (International Journal of Food and Nutritional Sciences, 2022)
Women entrepreneurs face lots of problems at start- up as well as during operating stage like, non-availability of finance, restricted mobility freedom and having to perform dual role, one at home and other at work. Technological advancement and information technology explosion have reduced the problem of women entrepreneursIn this study an attempt has been made to study the employment condition, demand and supply and occupation hazards / diseases of the women tailors in Valiyur block. Tirunelveli District. The study found that women tailors have been affected by back pain, skin diseases, eye problem, urinal infection and respiratory diseases. Preventive measures be followed to increase in productiveness. This will contribute to productivity, protection from occupational health problem, physical and mental well-being.